Comparison of the Surgical Approaches for Frontal Traumatic Intracerebral Hemorrhage - Eun Sung Park; Seong Keun Moon; Ki Seong Eom (Journal of Trauma and Injury)
Purpose Recent developments in minimally invasive techniques have the potential to reduce surgical morbidity, promote patient recovery, accelerate surgical procedures, and thus improve cost-effectiveness in case management. In this study, we compared the treatment efficacy and results of supraorbital keyhole approach (SOKA) with those of conventional unilateral frontal craniotomy (CUFC) for traumatic intracerebral hemorrhage (TICH) in the frontal lobe. Methods We analyzed the data of 38 patients who underwent CUFC (n=30) and SOKA (n=8) and retrospectively reviewed their medical records and radiological findings. Furthermore, we tried to identify the best surgical method for such lesions by including patients who underwent burr hole aspiration and drainage (BHAD) (n=9) under local anesthesia due to various circumstances. Results The difference in the initial Glasgow coma scale score, operative time, and length of hospitalization between the CUFC and SOKA were statistically significant. All radiological features between the two groups including associated skull fracture, amount of pre- and postoperative hematoma, percentage of complete hematoma removal, pre- and postoperative midline shifting of the hematoma, and development of postoperative delayed hematoma were not statistically significant. Our experience of 46 patients with TICH in the frontal lobe with any of the three different surgical methods including BHAD enabled us to obtain valuable findings. Conclusions Although it is difficult to insist that one particular approach is more useful than the other, we are confident that SOKA will have more advantages over CUFC in carefully selected patients with frontal TICH depending on the surgical experience of a neurosurgeon.